2015
DOI: 10.1002/art.39074
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage T1ρ and T2 Relaxation Times in Patients With Mild‐to‐Moderate Radiographic Hip Osteoarthritis

Abstract: Objective. To analyze region-specific T1r and T2 relaxation times of the hip joint cartilage in relation to presence or absence of radiographic hip osteoarthritis (OA) and presence or absence of magnetic resonance imaging (MRI)-detected cartilage defects.Methods. Weight-bearing radiographs and 3T MRI studies of the hip were obtained from 84 volunteers. Based on Kellgren/Lawrence (K/L) scoring of the radiographs, 54 subjects were classified as healthy controls (K/L grade £1) and 30 were classified as having mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 38 publications
4
49
4
Order By: Relevance
“…Progression of hip OA, defined as new or increased severity of cartilage lesions between baseline and 18 months, was assessed using an MR-based semiquantitative scoring system (SHOMRI). In contrast to radiographs, which have been used in previous studies to define OA severity and progression, SHOMRI can reliably identify subtle morphologic changes associated with hip OA 7,10,34,35 . This sensitivity is shown reflected by the difference in SHOMRI cartilage scores between progressors and non-progressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Progression of hip OA, defined as new or increased severity of cartilage lesions between baseline and 18 months, was assessed using an MR-based semiquantitative scoring system (SHOMRI). In contrast to radiographs, which have been used in previous studies to define OA severity and progression, SHOMRI can reliably identify subtle morphologic changes associated with hip OA 7,10,34,35 . This sensitivity is shown reflected by the difference in SHOMRI cartilage scores between progressors and non-progressors.…”
Section: Discussionmentioning
confidence: 99%
“…At follow-up, the hip scanned at baseline was re-scanned for each subject. The MRI protocol included intermediate-weighted fat-suppressed fast spin-echo (FSE) sequences in sagittal, oblique coronal, and oblique axial orientations, following the protocol described by Wyatt et al 10 . These sequences were used for semi-quantitative clinical grading of OA-related abnormalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that ultrasound detected inflammatory features, including synovial thickening, effusion and power Doppler signal, especially when persistently 3 Radiography Hip and pelvic geometry are associated with the risk of compartment-specific knee OA Thomas GE, et al 49 Radiography Cam-type FAI and acetabular dysplasia predict development of hip OA and joint replacement High bone mineral density is associated with knee and hip OA Hardcastle SA, et al 4e6 Radiography High BMD Z scores are associated with increased prevalence of hip and knee OA, specifically osteophytosis Potential new approaches to examining joint structures Turunen M, et al 7 CT CBCT can measure volumetric BMD of cortical, trabecular, and subchondral trabecular bone Kokkonen HT, et al 8 CT Arthrographic images enables sensitive detection of cartilage lesions Riecke BF, et al 10 US Ultrasound score is reliable and valid in detecting knee OA Abraham AM, et al 14 US US demonstrates higher prevalence of osteophytes in hand and hip OA than radiographic studies Liukkonen J, et al 15 US Arthroscopic ultrasound imaging quantitatively evaluates articular cartilage Hirata Y, et al 16 Kobayashi N, et al 17 PET 18F-fluoride uptake is associated with mechanical stress in hip OA and can detect bone abnormalities earlier than MRI Ultrasonographic abnormalities correlate with clinical endpoints Hall M, et al 11 US Effusion and synovial hypertrophy are more common in knee OA, with severity correlating with radiographic severity of knee OA Birn J, et al 12 US Large joint effusions correlates with rapidly destructive hip OA Malas FU, et al 13 US Meniscal bulging is associated with radiographic joint space narrowing and KL grades What is new in magnetic resonance imaging? Morphological structural abnormalities predict clinical endpoints Sharma L, et al 19 MRI Cartilage damage, BMLs, meniscal tears, and meniscal extrusion are associated with prevalent frequent knee symptoms and/or incident persistent symptoms Roemer FW, et al 21 MRI Cartilage damage, BMLs, meniscal damage, synovitis and effusion predicted short-term need for knee joint replacement Eckstein F, et al 22 MRI Accelerated cartilage thickness loss is greatest closest to the time of knee replacement Composition of cartilage influences morphometry Crema MD, et al 25 MRI Poorer dermis endpoints are associated with increased cartilage thickness, potentially representing "cartilage swelling" Ukiah T, et al 26 MRI Diffusion tensor imaging can distinguish early cartilage damage Wyatt C, et al 28 MRI T1r and T2 relaxation times of hip cartilage are associated with cartilage defects and radiographic hip OA Crema MD, et al 29…”
Section: Mri and Ultrasound Findings Predict Progression Of Hand Oa Amentioning
confidence: 99%
“…However, most of these studies have been performed at the knee joint, which is the joint with thickest cartilage in the appendicular skeleton [18]. Furthermore, T 1ρ and T 2 relaxation has been recently used to assess biochemical composition of cartilage in the knee [9; 10] and hip [11; 12] and potentially detect cartilage at risk of developing OA before the irreversible changes of OA occur in the morphological images [13; 14]. …”
Section: Introductionmentioning
confidence: 99%